Agung Nugroho's Political Strategy For Achieving A Majority Of Votes In The 2019 Riau Election - Diar, Muhammad; Ory Syafari Jamel Sutiyan; Nugroho Noto Diharjo; Adlin; Yulius Luturmas (POLITICO, 2023)
Agung Nugroho is a Democratic Party legislative candidate who won the highest vote in the Pekanbaru City I electoral district in the 2019 Riau Province DPRD member election with 27,527 votes. So the purpose of this study is to find out Agung Nugroho's modalities and Agung Nugroho's political strategy in winning the most votes in the election of members of the Riau Provincial DPRD in 2019. This research is a descriptive study with a qualitative approach. The location of this research was conducted in Pekanbaru City. The data collection technique used is through interviews and documentation. The data analysis technique used is an interactive analysis model. The results of the study concluded that based on the observations and analysis of the researchers were 1). Agung Nugroho's most powerful modality in the 2019 Riau Provincial DPRD legislative election was Political Capital. 2). The Offensive Strategy is the strategy used by Agung Nugroho in an effort to get the most votes in the 2019 Riau Provincial DPRD election